Clinical Features and Risk Factors Analysis for Hemorrhage in Adults on ECMO - Hu, Wenwen; Zhang, Jing; Wang, Meifang; Chen, Wei; Chai, Lin; Leung, Elaine Lai-Han; Tang, Yijun (Frontiers in Medicine, 2021)
Background: The use of extracorporeal membrane oxygenation (ECMO) to support critically ill patients with cardiorespiratory dysfunction is increasing over the last decades. However, hemorrhagic complications remain occurring frequently during ECMO support, which have a significant impact on morbidity and mortality. Methods: A retrospective study was performed on the 60 patients, who were admitted to the Taihe hospital in Shiyan City, Hubei Province from February 2017 to October 2020. Including 18 patients developed hemorrhage complications and 42 patients did not. Demographic, laboratory tests, clinical manifestations prior to ECMO were collected to analysis the clinical features. Univariable and multivariable logistic analysis methods were used in our study to explore the risk factors for hemorrhage in adults on ECMO. ROC curve was used to evaluate the predictive of binary Logistic model. Comparing the blood transfusions between the two groups. Analysed the results of APTT, PLT, HGB before ECMO operated and bleeding occurred. Results: Logistic analysis showed that the longer duration of ECMO support, the higher APTT and lower PLT prior to ECMO were independent factors for hemorrhage in adults on ECMO. In addition, we found that cannula site was the most common bleeding site. Most bleeding events occurred within the first three days of ECMO therapy. After operation, APTT was prolonged while PLT and HGB were decreased. The amount of blood transfusion in the bleeding group was higher than that in the non-bleeding group significantly. Conclusions: Clinicians should evaluate the risk of hemorrhage based on patients' coagulation function, underlying disease as well as the duration of ECMO support. Especially in the first three days during ECMO support. Special attention should be given on cannula site, mucosal, dermal and digestive tract to alert hemorrhage. Raising the PLT transfusion threshold and determining the amount of blood transfusion accurately may prevent bleeding events effectively.